Risk factors for biliary tract events during elective cholecystectomy waiting time after endoscopic retrograde cholangiopancreatography for choledocholithiasis - Tatsunori Satoh; Junichi Kaneko; Shinya Kawaguchi; Yuya Ishiguro; Shinya Endo; Naofumi Shirane; Hideyuki Kanemoto; Takanori Yamada; Kazuya Ohno (DEN Open)
Abstract Objectives Endoscopic lithotripsy and elective cholecystectomy, followed by endoscopic retrograde cholangiopancreatography, are the first‐line treatments for patients with common bile duct (CBD) stones (CBDS) and gallstones. However, this approach entails acute cholecystitis and recurrent cholangitis risk while patients await surgery. We aimed to identify acute cholecystitis and cholangitis risk factors during the waiting time for elective cholecystectomy. Methods This study comprised 151 patients with CBDS combined with gallstones who underwent cholecystectomy within 90 days of the first endoscopic retrograde cholangiopancreatography at two tertiary care centers between January 2019 and October 2021. Results The incidence of biliary tract events (acute cholecystitis, acute cholangitis, or any complications requiring unplanned cholangiopancreatography) was 28% (43 cases). In univariate and multivariate analyses, plastic stent placement as a bridge to surgery for the first treatment of CBDS was an independent risk factor for biliary tract events during the waiting time for surgery (odds ratio 4.25, p = 0.002). A subgroup analysis among those with plastic stent placement revealed a CBD diameter of ≤ 10 mm as an independent risk factor for acute cholecystitis (odds ratio 4.32; p = 0.027); a CBD diameter ≥ 11 mm was an independent risk factor for acute cholangitis and unplanned re‐endoscopic retrograde cholangiopancreatography (odds ratio 5.66; p = 0.01). Conclusions Plastic stent placement for CBDS before elective cholecystectomy increases the risk of acute cholecystitis or acute cholangitis during the waiting time for elective cholecystectomy.